Preoperative underweight is associated with adverse postoperative events in patients undergoing microvascular reconstruction surgery for oral and maxillofacial cancer. Issue 5 (May 2021) - Shida, A.; Ida, M.; Ueda, M.; Kirita, T.; Kawaguchi, M.
Abstract: We aimed to describe the prevalence of postoperative complications and evaluate its relationship with underweight, obesity, preoperative nutritional status, and systemic inflammation status in patients undergoing microvascular reconstruction for oral and maxillofacial cancer. Patients who were ≥20 years old and underwent microvascular reconstruction surgery between January 2009 to June 2019 were investigated. Patient demographics including body mass index, prognostic nutritional status, and neutrophil-lymphocyte ratio were collected. Logistic regression analysis was applied to evaluate these impacts on postoperative complications. A postoperative complication was defined as a Clavien–Dindo classification more than or equal to II. Of the 145 patients included in the analysis, 83 patients (57.2%) experienced postoperative complications, belonging to a Clavien–Dindo classification Ⅱ ( n  = 71), Ⅲb ( n  = 11), and Ⅳa ( n  = 1). Multiple logistic regression revealed that a body mass index less than 18.5 kg/m 2 (odds ratio 6.19, 95% confidential interval 1.34–28.6, P = 0.02) was related to postoperative complications. Another multiple logistic regression model including all explanatory factors found that underweight ( P  = 0.03) was related to postoperative complications. This retrospective study showed that preoperative underweight was associated with postoperative complications as evaluated by the Clavien–Dindo classification.